Determination of chloride in admixtures and aggregates for concrete by flow injection potentiometry - Junsomboon, Jaroon; Jakmunee, Jaroon (Bulletin of Applied Sciences, 2015)
A simple flow injection system using three 3-way solenoid valves as an electric control injection valve and with a simple home-made chloride ISE based on Ag/AgCl wire as a sensor for determination of chloride in admixtures and aggregates for cement has been developed. A liquid sample or an extract was injected into a water carrier stream which was then merged with 0.1 M KNO3 stream and flowed through a flow cell where the solution will be in contact with the sensor, producing a potential change recorded as a peak. A linear calibration graph in range of 10 - 100 mg [ was obtained with a detection limit of 2 mg L-1. Relative standard deviation for 7 replicates injecting of 20, 60 and 90 mg L-1 chloride solution was 1.0,1.2 and 0.6 % respectively. Sample throughput of 60 h-1 was achieved with the consumption of 1 mL each of electrolyte solution and water carrier. The developed method was validated by the British Standard methods.